CONTEMPORARY INDONESIAN ISLAMIC CIVILIZATION IN SUPPORTING PEACE IN ASEAN - Alfaizi, Faldin Fahza; Aida Husnia, Masna Binta; Ulum, Bahrul; Fihris, Fihris; Nasikhin, Nasikhin (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This study aims to analyze Contemporary Indonesian Islamic Civilization in Supporting Peace in ASEAN. This study using library research produces research data that; (1) The existence of Indonesian Islam which has peaceful and moderate characteristics supports the establishment of a peaceful situation in ASEAN. (2) Differences between Indonesian Islam and several ASEAN member countries result in differences in social life. (3) Indonesian Islam and its contribution to the global civilization of Indonesian Islam. This study has implications for learning how to increase Islamic peace in ASEAN which is being pursued at the lecture level.